PUASA MENGENDALIKAN NAFSU MENGUATKAN AKAL DAN AGAMA - Muhith Muhammad Ishaq (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
This research aims to interpret what the benefits of fasting are in controlling lust and increasing the role of reason and religion of human beings. Because fasting not only refrains from eating and drinking all day, but is an important pillar in the formation of a society with noble and superior character. This research method is qualitative by collecting primary and secondary data sourced from literature, namely the Qur'an, books of tafsir, hadith, Sirah Nabawiyah, journals, and research published online. The conclusion of the study is that with fasting, human passions will be controlled, their minds will strengthen and develop and the values of faith in their souls will be stronger.